Telling Queen Michal's story : an experiment in comparative interpretation - Clines, David J. A.; Eskenazi, Tamara Cohn (Journal for the study of the Old Testament. Supplement series, 1991)
This book, an anthology of previously published writing about Michal together with some new and original essays, is something of an experiment. Its purpose is to provide reders with raw materials for developing their own reading of the Michal story. It does not offer a unified portrait of this biblical character, but rather invites readers to form their own assessment interactively with these readings of the Michal story. At the same time, this book presents some systematic guidance for coping with these divergent interpretations of the complex and tantalizing figure of Michal.